2017
DOI: 10.1080/10410236.2017.1339370
|View full text |Cite
|
Sign up to set email alerts
|

Sentiment Analysis of an Online Breast Cancer Support Group: Communicating about Tamoxifen

Abstract: A better understanding of the breast cancer online narrative is important for a clearer conceptualizing of the role of online platforms in mediating health related support. Sentiment analysis was conducted on a breast cancer online support group regarding Tamoxifen to understand users’ emotions and opinions. This analysis was then contextualized within online social support literature. Out of the 498 users, the most active users were 80% more positive than least active users while least active users were 48% m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
43
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 40 publications
(45 citation statements)
references
References 40 publications
2
43
0
Order By: Relevance
“…Thus, including significant others in adherence interventions could maximize patients' perceptions of support and approval. Breast cancer survivors share experiences, emotions, and information about AET in online groups . A case study of an online discussion thread on tamoxifen showed how one survivor initiated treatment due to peer pressure .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, including significant others in adherence interventions could maximize patients' perceptions of support and approval. Breast cancer survivors share experiences, emotions, and information about AET in online groups . A case study of an online discussion thread on tamoxifen showed how one survivor initiated treatment due to peer pressure .…”
Section: Discussionmentioning
confidence: 99%
“…The importance of self-efficacy coincides with the meta-analysis of adherence in chronic conditions 10 ences, emotions, and information about AET in online groups. 36 A case study of an online discussion thread on tamoxifen showed how one survivor initiated treatment due to peer pressure. 37 Further research on this area is necessary.…”
Section: Discussionmentioning
confidence: 99%
“…Research results from this area of study have been mixed. Whereas a study shows that engagement with breast cancer support groups has the potential to promote empathy and the formation of personal relationships based on shared experiences [48], other studies suggest that the benefits of such groups can be exclusive, and the benefits of engagement are not distributed evenly among participants [49,50]. Nevertheless, the considerable variation within Facebook with respect to the media, and varied mechanisms of support exchange can make it difficult to differentiate types of behaviors observed on the Web and link those patterns with health benefits [1].…”
Section: Introductionmentioning
confidence: 99%
“…Of the remaining 99, 89 were excluded as they were not analysing at least one of the required topics of pharmacotherapy, medicine, or social media. A total of 10 studies were finally included (Figure 1) 20‐29 …”
Section: Resultsmentioning
confidence: 99%
“…Data pre‐processing was employed by five of the studies 20,21,23,24,27 . The methods used by the studies varied, with tokenization (breaking sentences into small word groups or phrases that are more easily read by a program) being common.…”
Section: Resultsmentioning
confidence: 99%